2010
DOI: 10.1021/jm100459k
|View full text |Cite
|
Sign up to set email alerts
|

[NiII(3-OMe-salophene)]: A Potent Agent with Antitumor Activity

Abstract: In this study, we investigated the anticancer properties of methoxy-substituted nickel(II)(salophene) derivatives. We demonstrated that the most active complex [NiII(3-OMe-salophene)] is not necrotic in Burkitt-like lymphoma cells (BJAB) and human B-cell precursor cells (Nalm-6). [NiII(3-OMe-salophene)] inhibited proliferation and induced apoptosis in a concentration dependent manner, giving evidence for the involvement of CD95 receptor-mediated, extrinsic pathway. Furthermore, [NiII(3-OMe-salophene)] overcame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 19 publications
0
17
0
1
Order By: Relevance
“…They display IC50 values in 2-5 μM range and also in general they produce lower side effect than thiosemicarbazones. In 2010, new methoxy-substituted nickel(II)(salophene) derivatives are synthesized and their anticancer properties were investigated (Lee et al, 2010). It was demonstrated that the most active complex [Ni(II)(3-methoxy-salophene)] (Fig 10) is not necrotic in Burkitt-like lymphoma cells (BJAB) and human B-cell precursor cells (Nalm-6).…”
Section: Fig 2 Structures Of Carboplatin (Left) and Oxaliplatin (Rimentioning
confidence: 99%
“…They display IC50 values in 2-5 μM range and also in general they produce lower side effect than thiosemicarbazones. In 2010, new methoxy-substituted nickel(II)(salophene) derivatives are synthesized and their anticancer properties were investigated (Lee et al, 2010). It was demonstrated that the most active complex [Ni(II)(3-methoxy-salophene)] (Fig 10) is not necrotic in Burkitt-like lymphoma cells (BJAB) and human B-cell precursor cells (Nalm-6).…”
Section: Fig 2 Structures Of Carboplatin (Left) and Oxaliplatin (Rimentioning
confidence: 99%
“…Gold(III) complexes with chelating N‐donor ligands are the first gold(III) complexes examined for anticancer applications, in vitro pharmacological studies point out that some of these novel gold(III) complexes are highly cytotoxic toward cultured human tumor cell lines, pyridine‐based complexes were tested in vitro against a panel of cancer cell lines and HeLa cancer cells . Palladium(II), nickel(II), and copper(II) complexes also were very promising candidates for anticancer therapy, this idea was supported by a number of research articles relating the synthesis and cytotoxic activities of numerous Pd(II), Ni(II), and Cu(II) complexes…”
Section: Introductionmentioning
confidence: 99%
“…Salans, salalens and in particular salens are most prominent ligands in coordination chemistry, and many of their metal complexes have shown potent antitumor activity (Scheme 1 , top) (Grutzke et al 2015 ; Hopff et al 2020 ; Immel et al 2011 , 2012a , b ; Lee 2010 , 2011 ; Meker et al 2011 ; Mir et al 2017 ; Peri et al 2011 ; Terenzi 2016 ). However, earlier work of ours on Mo-complexes had revealed that the biological activity may actually reside in the ligand.…”
Section: Introductionmentioning
confidence: 99%